SELF-IDENTIFICATION OF THREE BILINGUAL LANGUAGE TEACHERS: A MULTI-CASE STUDY - Eryılmaz, Rukiye (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*288.79px); top: calc(var(–scale-factor)*75.38px); font-size: calc(var(–scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.3668);" role="presentation">http://<span dir="ltr" style="left: calc(var(–scale-factor)*312.55px); top: calc(var(–scale-factor)*75.38px); font-size: calc(var(–scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.12476);" role="presentation">dx.doi.org/10.7220/2335-<span dir="ltr" style="left: calc(var(–scale-factor)*404.86px); top: calc(var(–scale-factor)*75.38px); font-size: calc(var(–scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.10321);" role="presentation">2027.9.2 Identity, as a complex and relative notion, is extremely hard to define, especially when it comes to bilingual people who are to cope with two or more identities. The relationship between language and identity is already intricate, and those who are born into bilingual families not only deal with these lingual complexities, but also social diversities. Starting from this point, this qualitative multi-case study addresses the issue of identity through the in-depth analysis of three bilinguals who are also second language teachers at a private foundation university. The data were collected mainly through face-to-face semi-structured interviews, and similar and different themes were revealed by within-case and cross case analysis. The participants reflected on how they labeled themselves in terms of their identities as bilinguals. Finally, the research revealed that family bonds and emotions, as well as social norms and language, played various roles in the self-identification of bilinguals. The fact that the acculturation and integration strategies of the participants were different and that self-identification was remarkably subjective and flexible were the other underlying outcomes of the research.